2016
DOI: 10.1111/jop.12436
|View full text |Cite
|
Sign up to set email alerts
|

Could the PI3K canonical pathway be a common link between chronic inflammatory conditions and oral carcinogenesis?

Abstract: The association between chronic inflammatory disorders and oral carcinogenesis has been both a source of interest and contention. Based upon its central importance in oral carcinogenesis, the finding that the PI3k/Akt/mTOR pathway is activated in oral lichen planus, chronic graft-versus-host disease, and chronic oral candidiasis suggests that it may provide a link between benign and malignant oral conditions. Here, we discuss a possible mechanistic rationale that addresses the activation of this important sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
(52 reference statements)
2
9
0
Order By: Relevance
“…Our results showed that PI3K inhibitor treatment attenuates the inflammatory cell infiltration in experimental AAAs. The Wortmannin can reduce influx of the CD3 + T cells and CD31 + blood vessels as previous described 26 , 29 . In our study, PI3K inhibition treatment significantly reduced aortic macrophage infiltration while suppressing AAA formation and progression, as the CD68 + macrophages in Wortmannin group is less than the Vehicle one.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our results showed that PI3K inhibitor treatment attenuates the inflammatory cell infiltration in experimental AAAs. The Wortmannin can reduce influx of the CD3 + T cells and CD31 + blood vessels as previous described 26 , 29 . In our study, PI3K inhibition treatment significantly reduced aortic macrophage infiltration while suppressing AAA formation and progression, as the CD68 + macrophages in Wortmannin group is less than the Vehicle one.…”
Section: Discussionsupporting
confidence: 59%
“…Early findings confirm and extend prior observations regarding wortmannin in the treatment of cancer 24 , 25 . As recently document indicates a potential important role of PI3K/AKT pathway in inflammation 26 , 27 , it is rational to question whether PI3K inhibitor could limits the progression of AAA. Our results demonstrate for the first time that Wortmannin, a prototype and classical PI3K inhibitor, suppresses PI3K/AKT pathway and prevents the formation and progression of experimental abdominal aortic aneurysm in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is believed that Genipin inhibits OSCC cells growth and improves the autophagy through suppressing PI3K/Akt/mTOR signaling pathway, and PI3K/Akt/mTOR pathway is an attractive target for the treatment of OSCC. 39 Conclusively, this study showed that Genipin inhibited the cells' viability, induced apoptosis, and promoted autophagy in OSCC, and its mechanism might be related to the inhibition of PI3K/Akt/mTOR signaling pathway. It provided a new candidate for OSCC drug treatment.…”
Section: Discussionmentioning
confidence: 71%
“…The gain of function mutations in the upstream gene, phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA), induces the oncogenic transformation of the AKT/mTOR signaling, leading to metabolic reprogramming in cells and subsequently causing OC development [101,102]. In 2016, Sonis and Mendes also postulated that the AKT/mTOR pathway drove the transformation of oral cells from benign to the malignant stage [103].…”
Section: Role Of Akt/mtor Pathway In Different Cellular Processes Of mentioning
confidence: 99%